Comparison of different demodulator fliters for sigma-delta modulator - Xue, Yao. (2008)
Sigma-Delta modulators have been widely used in the implementation of high quality A/D and D/A converters. Recently Sigma-Delta modulators have become popular in a number of other signal processing applications. Some of these applications can be found in digital filtering, frequency synthesis, phase locked loop design, signal generation and synchronizer design.